Influence of polyethylene glycol molecular weight on the anticancer drug delivery of pH‐sensitive polymeric micelle. Issue 32 (24th April 2019) - Shan, Xiaotian; Mao, Jing; Long, Miaomiao; Ahmed, Kamel S.; Sun, Changling; Qiu, Lipeng; Chen, Jinghua
ABSTRACT: Polyethylene glycol (PEG) and pH‐sensitive polymers have been widely utilized in anticancer drug delivery systems due to their characteristics of prolonging circulation time and tumor‐responsive drug release. However, the effect of PEG molecular weight on the delivery of anticancer drug‐encapsulating pH‐sensitive polymer micelles has been poorly studied. Therefore, a simple method was used to prepare pH‐sensitive doxorubicin (DOX)‐loaded micelles (DOX/POD) based on polyethylene glycol‐2‐(octadecyloxy)‐1, 3‐dioxan‐5‐amine (POD) polymers, and the influence of PEG molecular weights (1 K, 2 K, and 5 K) on in vitro drug release and antitumor effect was further studied. Interestingly, as the molecular weight increased, the release amount of DOX was augmented. While the cytotoxicity and cellular uptake were increased, the molecular weight was decreased. It is reasonable to speculate that the high molecular weight of PEG may promote the dissolution rate of DOX, and their micelles with uncompact structure are being prone to disassembly in an acid environment. However, the low molecular weight of PEG may contribute to the formation of compact POD micelles, which make it easier to be uptaken by tumor cells resulting in the enhanced antitumor effect. Taken together, the results indicate that pH‐sensitive POD micelles with low molecular weight can achieve the efficient delivery of drugs, and PEG molecular weight in pH‐sensitive nanocarriers may influence the antitumor effect. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47854. Abstract : pH‐sensitive DOX/POD micelles were taken up into tumor cells and disassembled in cytosol to release DOX into nucleus